2014
DOI: 10.1111/jgh.12434
|View full text |Cite
|
Sign up to set email alerts
|

Role of glycine N‐methyltransferase in experimental ulcerative colitis

Abstract: Collectively, our findings suggest that GNMT may be a crucial molecule in the pathogenesis of DSS-induced colitis. This finding may provide new information for a potential therapeutic target in treating IBD.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
9
0

Year Published

2014
2014
2022
2022

Publication Types

Select...
5

Relationship

3
2

Authors

Journals

citations
Cited by 6 publications
(9 citation statements)
references
References 31 publications
(78 reference statements)
0
9
0
Order By: Relevance
“…In addition, Gomez-Santos et al reported that functional loss of GNMT augmented NK cell-mediated inflammation and exacerbated endotoxin-induced acute liver injury (13). Moreover, absence of GNMT exacerbated the deregulation of the inflammatory response in an experimental ulcerative colitis model (12). Collectively, these evidences suggested that GNMT exerts protective antiinflammatory effects in acute inflammation models and during activation of innate immune responses.…”
Section: Discussionmentioning
confidence: 98%
See 1 more Smart Citation
“…In addition, Gomez-Santos et al reported that functional loss of GNMT augmented NK cell-mediated inflammation and exacerbated endotoxin-induced acute liver injury (13). Moreover, absence of GNMT exacerbated the deregulation of the inflammatory response in an experimental ulcerative colitis model (12). Collectively, these evidences suggested that GNMT exerts protective antiinflammatory effects in acute inflammation models and during activation of innate immune responses.…”
Section: Discussionmentioning
confidence: 98%
“…In Gnmt and apolipoprotein E double knockout mice, GNMT deficiency modulated the functions of macrophages and exacerbated the pathogenesis of hyperlipidemia, inflammation and atherosclerosis, indicating that GNMT regulates the inflammatory responses by modulating the function of macrophages (11). Moreover, GNMT deficiency increased the susceptibility to dextran sulfate sodium (DSS)-induced colitis in mice (12). Natural killer (NK) cells from Gnmt -/mice were activated spontaneously, expressed more tumor necrosis factor (TNF)-related apoptosisinducing ligand (TRAIL) and had stronger cytotoxic activity, suggesting that they contributed to a proinflammatory environment in the liver (13).…”
Section: Introductionmentioning
confidence: 99%
“…Leukocyte infiltration and cytokine production as indicators of inflammatory status are crucial in determining the stages of certain inflammatory diseases [ 14 , 24 ]. These key inflammatory events can trigger the process of tissue remodeling and fibrosis such as cell proliferation and apoptosis, epithelial-mesenchymal transition (MET), fibroblast activation, and extracellular matrix deposition [ 16 , 17 ].…”
Section: Discussionmentioning
confidence: 99%
“…Importantly, oxidative stress is known to be highly associated with the regulation of inflammation in a variety of inflammatory diseases [ 14 , 18 ]. This notion was further supported by our findings that the levels of superoxide anion radical and hydrogen peroxide in UUO kidneys were increased in WT mice, which was reduced in UUO kidneys of sEH −/− mice.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation